Hydrogels Smart Materials for Biomedical Applications - Popa, Lăcrămioara; Violeta Ghica, Mihaela; Dinu-Pîrvu, Cristina-Elena (IntechOpen, 2019)
Hydrogels, as three-dimensional polymer networks, are able to retain a large amount of water in their swollen state. The biomedical application of hydrogels was initially hampered by the toxicity of cross-linking agents and the limitations of hydrogel formation under physiological conditions. However, emerging knowledge in polymer chemistry and an increased understanding of biological processes have resulted in the design of versatile materials and minimally invasive therapies.The novel but challenging properties of hydrogels are attracting the attention of researchers in the biological, medical, and pharmaceutical fields. In the last few years, new methods have been developed for the preparation of hydrophilic polymers and hydrogels, which may be used in future biomedical and drug delivery applications. Such efforts include the synthesis of self-organized nanostructures based on triblock copolymers with applications in controlled drug delivery. These hydrogels could be used as carriers for drug delivery when combined with the techniques of drug imprinting and subsequent release. Engineered protein hydrogels have many potential advantages. They are excellent biomaterials and biodegradables. Furthermore, they could encapsulate drugs and be used in injectable forms to replace surgery, to repair damaged cartilage, in regenerative medicine, or in tissue engineering. Also, they have potential applications in gene therapy, although this field is relatively new.